1994
DOI: 10.1159/000292565
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Transplacental Hemorrhage in Patients with Threatened Abortions

Abstract: The frequency and volume of transplacental hemorrhage that occurs with threatened abortions is unknown. The use of Rh immune globulin for such patients is therefore undefined. We studied the incidence and quantity of transplacental hemorrhage in patients with threatened abortions and in a control population of patients presenting in the first 20 weeks of pregnancy without a history of bleeding. Using the Kleihauer-Betke test, the incidence of transplacental hemorrhage in our control and study population was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…Even though the number of patients in this study was small, it satisfied the estimated sample size. Furthermore, previous studies showed no significant differences in HbF% in maternal circulation in the first trimester in patients with threatened miscarriage [12, 14, 15, 22].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Even though the number of patients in this study was small, it satisfied the estimated sample size. Furthermore, previous studies showed no significant differences in HbF% in maternal circulation in the first trimester in patients with threatened miscarriage [12, 14, 15, 22].…”
Section: Discussionmentioning
confidence: 88%
“…There was a higher rate of patients with FMH in the VB group (11.24%) compared to the asymptomatic patients (4.26%); however, the difference was not significant ( p = 0.13). In a methodologically similar study, Kuller et al [22] compared patients with threatened miscarriage and asymptomatic control patients using Kleihauer-Betke test and deemed positive the HbF% greater than or equal to 0.04. They found a positive rate for FMH of 4.1 and 4.4% in the bleeding and CG, respectively, and as Von Stein et al [7], they did not find significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura é ainda muito controversa em relação ao risco de aloimunização e uso da imunoglobulina RhD para sua profilaxia nos casos de ameaça de abortamento no primeiro trimestre 5,36,46,69,70 . Nas diversas publicações sobre o tema, os defensores da administração da imunoglobulina o fazem sob a justificativa do baixo risco da medicação frente ao alto risco de complicação gestacional na aloimunização.…”
Section: Aplicabilidade Do Estudounclassified
“…Os grupos não foram diferentes em relação à porcentagem de pacientes que apresentaram alguma porcentagem de eritrócitos fetais circulantes diferente de zero, entre as pacientes no grupo com HIU foram 68,2%, na ameaça de abortamento 76,5% e entre as assintomáticas 74,1% com HbF% positivo na circulação (p=0,830).Quando se realizou a conversão de HbF% em volume de HFM, o grupo que apresentou menor mediana de volume transferido foi o de pacientes com sangramento vaginal com mediana de 0,13 ml de sangue fetal circulante. Mesmo a diferença não sendo significativa entre os grupos, pelos estudos realizados previamente4,46 em pacientes com ameaça de abortamento, esse era o grupo em que se esperava encontrar maior HbF%.Von Stein et al (1992) 4 compararam pacientes com ameaça de abortamento e pacientes sem antecedentes de sangramento que internavam para abortamento eletivo. Utilizaram um grupo de pacientes não gestantes de idade pareada para definir, por meio do teste de K-B, um valor mínimo de 0,07 de HbF% de maneira que pacientes com HbF% ≥ 0,07 seriam consideradas positivas.…”
unclassified